Coffee Machine Rental Business Model Analysis: Exploring Market Opportunities and Business Development Strategies - Frans Sudirjo (Westscience Press, 2023)
This research paper explores the business model analysis of coffee machine rental services in Bandung City, focusing on market opportunities and business development strategies. The study adopts a mixed-methods approach, incorporating qualitative and quantitative data collection methods. The findings reveal promising market opportunities within Bandung City's vibrant coffee industry, driven by the growing number of entrepreneurs and café owners seeking cost-effective solutions. Customer preferences and behavior analysis highlight the importance of high-quality coffee, consistent taste, efficiency, and convenience. The research identifies key business development strategies, including customer segmentation, value proposition, pricing, marketing, and partnerships. By implementing these strategies, coffee machine rental companies can effectively target customers, differentiate their services, optimize pricing, promote their offerings, and expand through collaborations. The research contributes to understanding the dynamics of the coffee machine rental market in Bandung City and provides valuable insights for industry players aiming to tap into its potential.